Modeling temperature dependent and absolute carbamate stability constants of amines for CO2 capture. (July 2020) - Gupta, Mayuri; Svendsen, Hallvard F.
Graphical abstract: Highlights: Temperature dependent Carbamate stability constants (Kc) for amines are calculated. Various composite, DFT and HF methods are employed for gas phase calculations. Solution phase calculations are done with implicit and explicit solvation models. Temperature effects on Kc are studied and compared against experimental data. The results can help to optimize the solvents for carbon capture and storage (CCS). Abstract: Thermodynamic properties and carbamate stability constants (Kc) for a dataset of 25 amines and alkanolamines, with desirable post combustion CO2 capture (PCC) solvent properties, have been studied extensively employing various gaseous phase calculations and solvation models. A comprehensive study of gaseous phase free energy and enthalpy is carried out using density functional methods [B3LYP/6-311++G(d, p)], and composite methods (G3MP2B3, G3MP2, G4MP2 and CBS-QB3). Implicit solvation models (PCM, SM8T and DivCon) and the Explicit Solvation Shell Model (ESS) were used to study solvation free energy of various neutral and ionic species present in the amine-carbamate formation reaction. Temperature dependent carbamate stability constants are calculated for the carbamate formation reaction of amines and alkanolamines to better understand the effect of temperature on temperature swing absorption-desorption PCC processes. The temperature dependency of Kc was compared against available experimental data.